Influence of experience and professional skepticism on audit judgement of government external auditors - Sumartono Sumartono; Yana Ermawati; Tania Meliana Rorong (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2022)
The complexity of public services require auditors to perform audit judgments to ensure the quality of information and to evaluate the evidence presented in financial statements. Thus, the auditors’ judgment and technical skills are important factors in audit quality. This study examines how auditor independence, task complexity, auditor experience, and professional skepticism affect auditor judgment. Purposive sampling was employed to select auditors who worked at the Supreme Audit Institution (BPK-RI) of Papua Province. The data were collected using a set of a questionnaire consisting of 30 items measured on a Likert scale, distributed directly and via Google Forms. The data analyzes using multiple linear regression. The result presents empirical evidence that auditor experience and professional skepticism partially affected audit judgment, whereas task complexity and auditor independence did not have a partial effect on audit judgment. The study provides relevant and adequate insights to government external auditors regarding the factors that should be taken into consideration in maintaining and improving their audit judgments to bring optimal benefits for the local government stakeholders.